2014
DOI: 10.7448/ias.17.4.19778
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome in HIV+ patients receiving 3‐ or 4‐drug regimens during PHI

Abstract: IntroductionThe optimal timing and modality of therapeutic intervention during early phases of HIV infection is still debated; in our prospective observational study we evaluated immunological and virological outcome in HIV+ patients treated during acute or recent HIV infection.Materials and MethodsA total of 25 naïve patients with acute (detectable HIV-RNA, immature Western Blot) or recent (documented infection within six months) HIV infection were recruited at the Infectious Diseases Units of the University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In the era of expanded ART options, another consideration is what regimen is appropriate to start during AHI. Observational and randomized studies comparing standard ART to "intensified" regimens that include integrase or entry inhibitors consistently demonstrate similar effectiveness in raising CD4 T-cell counts, and lowering markers of immune activation and cell-associated DNA [150][151][152][153]. Although intensified regimens may not be necessary to reap virological or immunological benefits, intensified regimens result in a more rapid VL decline in blood and genital secretions [154].…”
Section: Ideal Art Regimens For Ahimentioning
confidence: 99%
“…In the era of expanded ART options, another consideration is what regimen is appropriate to start during AHI. Observational and randomized studies comparing standard ART to "intensified" regimens that include integrase or entry inhibitors consistently demonstrate similar effectiveness in raising CD4 T-cell counts, and lowering markers of immune activation and cell-associated DNA [150][151][152][153]. Although intensified regimens may not be necessary to reap virological or immunological benefits, intensified regimens result in a more rapid VL decline in blood and genital secretions [154].…”
Section: Ideal Art Regimens For Ahimentioning
confidence: 99%
“…Several randomized studies comparing standard ART vs. regimens intensified with integrase and entry inhibitors showed plasma HIV RNA to decline more rapidly in the intensified arm; but all regimens were similarly effective in lowering cell-associated DNA and RNA and markers of immune activation as well as raising CD4+ T cell counts (49-51). Other non-randomized studies showed minimal to no benefit in intensifying standard ART regimens (67, 68). However, the more rapid viral load decline in blood and genital secretions with integrase inhibitor-based regimens may prove beneficial in reducing transmission risk during AHI (69).…”
Section: Antiretroviral Therapy For Acute and Early Hiv Infectionmentioning
confidence: 98%